Ageing-related bone and immunity changes: insights into the complex interplay between the skeleton and the immune system - Mi, Bobin; Xiong, Yuan; Knoedler, Samuel; Alfertshofer, Michael; Panayi, Adriana C.; Wang, Haixing; Lin, Sien; Li, Gang; Liu, Guohui (Bone research, 2024)
Ageing as a natural irreversible process inherently results in the functional deterioration of numerous organ systems and tissues, including the skeletal and immune systems. Recent studies have elucidated the intricate bidirectional interactions between these two systems. In this review, we provide a comprehensive synthesis of molecular mechanisms of cell ageing. We further discuss how age-related skeletal changes influence the immune system and the consequent impact of immune system alterations on the skeletal system. Finally, we highlight the clinical implications of these findings and propose potential strategies to promote healthy ageing and reduce pathologic deterioration of both the skeletal and immune systems.
Gesehen am 18.08.2025